SISTEM INFORMASI PENERIMAAN KARYAWAN BERBASIS WEB PADA PT. SINAR SOSROTANGERANG - Sulistiyah Sulistiyah; Rachmat Hidayat; Haryanto Haryanto (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Human resources is a very important factor in supporting the company's performance. Recruitment system that is conventional, which is part of the admin to manually choose a job application file to be recorded, less efficient and time-consuming and prone to errors. The systems in data processing applicants still used by admin of PT. Sinar Sosro. Information systems are made is a web-based information system that provides ease of data processing applicants by the personnel themselves as applicants to fill the data itself directly online. By using the Information System Web-Based Employee Recruitment is expected to assist the Human Resources Department PT. Sosro Sinar for data processing applicants, and the applicants can access job information and apply online